A century of carrier aviation the evolution of ships and shipborne aircraft - Hobbs, David 1946- (Naval Institute Press, 2009)
It is now almost exactly a hundred years since a heavier-than-air craft first took off and landed on a warship, and from the very beginning flying at sea made unique demands on men and machines. As warplanes grew larger, faster and heavier, air operations from ships were only possible at all through constant development in technology, techniques and tactics. This book charts the progress and growing effectiveness of naval air power, concentrating on the advances and inventions - most of them British - that allowed shipborne aircraft to match their land-based counterparts